Climate change and One Health. Issue 11 (4th April 2018) - Zinsstag, Jakob; Crump, Lisa; Schelling, Esther; Hattendorf, Jan; Maidane, Yahya Osman; Ali, Kadra Osman; Muhummed, Abdifatah; Umer, Abdurezak Adem; Aliyi, Ferzua; Nooh, Faisal; Abdikadir, Mohammed Ibrahim; Ali, Seid Mohammed; et al.
Abstract: The journal The Lancet recently published a countdown on health and climate change. Attention was focused solely on humans. However, animals, including wildlife, livestock and pets, may also be impacted by climate change. Complementary to the high relevance of awareness rising for protecting humans against climate change, here we present a One Health approach, which aims at the simultaneous protection of humans, animals and the environment from climate change impacts (climate change adaptation). We postulate that integrated approaches save human and animal lives and reduce costs when compared to public and animal health sectors working separately. A One Health approach to climate change adaptation may significantly contribute to food security with emphasis on animal source foods, extensive livestock systems, particularly ruminant livestock, environmental sanitation, and steps towards regional and global integrated syndromic surveillance and response systems. The cost of outbreaks of emerging vector-borne zoonotic pathogens may be much lower if they are detected early in the vector or in livestock rather than later in humans. Therefore, integrated community-based surveillance of zoonoses is a promising avenue to reduce health effects of climate change. Abstract : A One Health approach is advantageous for the adaptation to climate change effects on the health of humans and animals concurrently.